2003
DOI: 10.1303/aez.2003.487
|View full text |Cite
|
Sign up to set email alerts
|

Possible existence of a common temperature and a common duration of development among members of a taxonomic group of arthropods that underwent spaciational adaptation to temperature.

Abstract: Data sources. To examine the linearity between t and k, data for the temperature-dependent larval development of six groups, i.e., the family Tenebrionidae (10 species(s)/strains(s)), the family Pyralidae (8 s/s), the family Aphididae (13 s/s), the genus Periplaneta (4 s/s) and the genus Aedes (13 s/s) of insects, and the family Tetranychidae (12 s/s) of mites, were selected (see Table 1 and Appendix 1). The data on temperatures related to the induction of diapause (e.g., 20°C for Periplaneta fuliginosa report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…Shi et al (2010) found evidence supporting this hypothesis based on data on the developmental rate of egg and nymphal stages of Lygocoris lucorum Meyer-Dür. In addition Ikemoto (2003) proposed the common-intersection hypothesis (CIH), which states that the development times of the related members within a taxon (e.g., within a family) are equal at a given temperature. Therefore, the development rate lines of those species have a common intersection (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al (2010) found evidence supporting this hypothesis based on data on the developmental rate of egg and nymphal stages of Lygocoris lucorum Meyer-Dür. In addition Ikemoto (2003) proposed the common-intersection hypothesis (CIH), which states that the development times of the related members within a taxon (e.g., within a family) are equal at a given temperature. Therefore, the development rate lines of those species have a common intersection (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sample sizes used by Ikemoto (2003) were very small. The main objective of the present study was to compile additional temperature-dependent development rate data from two families, Aphididae and Tetranychidae, for testing the common-intersection hypothesis(CIH) with larger sample sizes through mathematical analysis on the basis of two linear relationships (i.e., the linear relationship between temperature and development rate and that between the lower developmental threshold and the sum of effective temperatures).…”
Section: Introductionmentioning
confidence: 99%
“…The upper (T H ) and lower (T L ) threshold temperatures were estimated at 36.4 and 11.2° C for total development, suggesting that the hypothetical enzyme was half active and half inactive at these thresholds. This could be one of the reasons for the incomplete development of the larval stage at 34 and 35° C. The intrinsic optimum temperature along with its confidence interval could be used as an indicator for the geographical distribution and place of origin of related species (Ikemoto 2003). This is also a potential tool for the construction of a phylogenetic tree within a taxon (Ikemoto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other ecophysiological and entomological approaches have been employed to explain the temporal occurrence of vectors by describing their life histories. These models calculate development according to air temperature at each developmental stage of the insect, based on the assumption that the growth of an insect depends on the temperature of its habitat (Hopp & Foley, 2001;Ikemoto, 2003;2005;2008;Depinay et al, 2004;Pascual et al, 2006). Temperature affects the survival of the parasite only during the life cycle of Anopheles mosquitoes.…”
Section: Biological Modelmentioning
confidence: 99%